High cycle life lithium ion battery cell with nanostructured silicon-containing anode

By using prelithiated silicon anode in the lithium-ion battery cell, the swelling problem caused by volume changes in the silicon anode in the lithium-ion battery cell is solved, and excellent cycle life and capacity properties are achieved.

CN119816953APending Publication Date: 2025-04-11LEYDENJAR TECH BV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380052441.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2023-07-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In existing lithium-ion battery cells, the swelling problem caused by volume changes during charging and discharging of silicon-containing anodes leads to rupture, shattering or layering of the anode material, reducing the charging capacity and cycle life.

Method used

By using a prelithiated silicon anode in a lithium-ion battery cell, the prelithiation level is 1% to 100% to form a silicon material with a columnar form, reducing internal stress and fracture, and maintaining a high surface area to accommodate lithium incorporation.

Benefits of technology

The excellent cycle life and capacity properties of lithium-ion battery cells are achieved, eliminating the need for in-situ sacrificing lithium ion sources, and reducing ablation of the solid-electrolyte interface layer, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231720560000351
    Figure BDA0005231720560000351
  • Figure BDA0005231720560000361
    Figure BDA0005231720560000361
  • Figure HDA0005231720570000011
    Figure HDA0005231720570000011
Patent Text Reader

Abstract

The present application relates to a method of manufacturing a lithium ion battery cell (12), comprising the steps of: (i) providing a silicon anode (6); (ii) pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of from 1% to 100%; (iii) providing a provider: a separator (2); an electrolyte; and a lithium ion cathode (3); (iv) forming a lithium ion battery cell from the pre-lithiated silicon anode (1), the separator (2) and the lithium ion cathode (3), where the silicon anode (6) comprises a lithium storage material, where the lithium storage material comprises between 70 wt.% and 100 wt.%, preferably between 85 wt.% and 100 wt.% of silicon relative to the lithium storage material, and where the lithium storage material comprises a silicon material having a columnar morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to lithium-ion cells in which the anode comprises pre-lithiated silicon, methods for their production, batteries comprising such cells and uses of such cells and / or batteries. Background of the Invention

[0003] A battery is a device consisting of one or more electrochemical cells with external connections that convert stored chemical energy into electrical energy. A battery cell has a positive and a negative electrode, also known as the cathode and anode, respectively. When the battery is connected to an external circuit, electrons flow from the anode to the cathode through the external circuit, thereby delivering electrical energy to the circuit and any devices connected to the circuit.

[0004] Primary batteries, such as alkaline batteries, are disposable because the electrode materials are permanently changed during discharge. Secondary batteries, such as lithium-ion batteries, can be charged and discharged many times because the original composition of the electrode materials can be restored by applying a reverse current.

[0005] A battery cell consists of two half-cells connected in series via a conductive electrolyte material. One of the half-cells contains the cathode, while the other half-cell contains the anode, and the electrolyte is present in both half-cells. A separator may be present between the two half-cells. The separator prevents a short circuit between the cathode and the anode while still allowing ions to move across the separator between the two half-cells.

[0006] A particularly advantageous type of electrochemical cell is the lithium-ion cell. In a lithium-ion cell, lithium ions move from the negative electrode or anode through the electrolyte to the positive electrode or cathode during discharge and back during charging. Lithium-ion cells have historically employed lithium intercalation compounds at the positive electrode and graphite at the negative electrode. Lithium-ion cells generally have a higher energy density than conventional lead-acid batteries, advantageously have no memory effect and generally exhibit low self-discharge.

[0007] Recent developments in lithium-ion battery cells have sought to use silicon in the anode material to replace the historically used graphite. This is because silicon allows for much higher maximum capacities than the approximately 370 mAh / g that can be achieved with graphite. For example, pristine silicon allows for a specific capacity of approximately 3600 mAh. Achieving higher charge capacities without significantly increasing weight is a key challenge for improving the battery life of mobile phones, drones or electric cars.

[0008] One factor slowing the widespread commercialization of lithium-ion battery cells with silicon-containing anodes is that silicon typically exhibits a large volume change upon lithium insertion, wherein the volume may increase by as much as 300% to 400%. This volume change typically induces large anisotropic stresses within the anode, which may cause the silicon material of the anode to crack, break, or delaminate. Cracking, breaking, or delamination of the silicon material of the anode reduces the charge capacity of the anode and reduces the charge cycle life of a battery cell containing such an anode.

[0009] To overcome these swelling issues, a range of three-dimensional silicon surface morphologies for anodes have been developed. One approach is to develop so-called nanostructured architectures, examples of which include three-dimensional thin films, nanowires, and nanotubes. Three-dimensional thin film silicon anodes adopt a geometry that is most similar to traditional thin film batteries, in which a thin film of silicon is deposited on a metal foil, which serves as a current collector. Thin film "two-dimensional" batteries are typically limited to a film depth of between 2 microns and 5 microns to avoid cracking, fragmentation, and / or delamination of the silicon layer, thereby limiting the areal capacity to be significantly less than that obtainable with three-dimensional thin films.

[0010] Three-dimensional thin films use the third dimension (corresponding to depth) to increase the electrochemically active area. One option for doing this is to etch perforations into the silicon film by inductively coupled plasma etching on silicon. Another option is to deposit silicon by plasma-enhanced chemical vapor deposition, so that a silicon film is deposited on a metal collector foil, wherein the film is mainly formed by silicon pillars extending perpendicular to the surface of the metal foil. Such pillars typically have a diameter of several hundred nanometers. Between the pillars is a network of voids or empty spaces. These nanostructured surface morphologies allow the pillars to swell, i.e., increase in volume, thereby extending into the voids. This means that when swelling, one pillar exerts little or no pressure on an adjacent pillar, which means that, in general, the bulk silicon material exerts little or no pressure parallel to the metal foil surface. This advantageously allows these materials with nanostructured surface morphologies to avoid cracking, breaking or delamination.

[0011] Nanowires and nanotubes may also be used. One such example is silicon nanowires grown on a rigid current collector substrate by a gas-liquid-solid process. The wires are attached to the current collector material at one end, and the irregular network of silicon wires is believed to allow for accommodation of large strains of swelling due to the incorporation of lithium. This advantageously allows these materials with nanostructured surface morphology to avoid cracking, fragmentation, or delamination.

[0012] In general, these silicon-containing anodes with three-dimensional surface morphology have a relatively high surface area of ​​the anode in contact with the electrolyte. This is advantageous on the one hand due to increased areal capacity.

[0013] In lithium-ion battery cells with silicon-containing anodes, the SEI plays a particularly important role in capacity degradation due to the large volume changes during cycling. The expansion and contraction of the anode material often ruptures the SEI layer formed on top of it, exposing more of the anode material to direct contact with the electrolyte, which leads to further SEI generation and further LLI. This reduces the commercially useful charge cycle life of lithium-ion battery cells with silicon-containing anodes. Due to the surface area and shape of the silicon material at the anode-electrolyte interface, this problem of SEI rupture is particularly severe for anodes containing silicon with nanostructured surface morphology.

[0014] Anodes comprising silicone and graphite components have been known for quite some time. Pre-lithiation processes when such an anode is included in a battery are also disclosed. For example, US2021126250 discloses a silicon / graphite anode prepared by slurry deposition. EP3561918 also discloses electrodes coated with silicon / graphite electrode slurry. WO2019113534A1 discloses an anode containing about 80wt% silicon particles, 5wt% graphite and 15wt% resin glassy carbon, which is laminated on copper foil. Each of these documents also discloses a way of pre-lithiation, however, a sacrificial lithium source is generally used.

[0015] Different strategies for forming anode materials involve constructing silicon in the form of nanostructures (such as nanoparticles, nanowires, nanotubes or more complex 3D structures). Through these nanostructures, silicon has ample space to accommodate volume expansion, reduce internal stress and fracture, while also maintaining a high surface area for lithium ions to be transferred from the electrolyte to the silicon. For example, WO2010129910A2 discloses a conductive substrate and a silicon-containing nanowire substrate fixed to the conductive substrate. WO2015175509A1 extends this concept by having two layers of silicon material coated with a nanowire template fixed to a substrate, wherein the second silicon layer has a higher density than the first layer. WO2015175509A1 points out that the first silicon layer thus provides space into which the silicon can expand when absorbing lithium, while the second silicon layer reduces the formation of the SEI layer.

[0016] During the first charge cycle of a lithium-ion battery cell operation, the electrolyte decomposes to form a series of generally ill-defined lithium-containing compounds on the surface of the anode, producing a layer called the solid-electrolyte interface (SEI). The solid-electrolyte interface layer is a result of the reduction potential of the anode. During cycling, a voltage is applied at which the electrons reduce some components of the electrolyte. Since the SEI layer is formed in part by lithium-containing compounds, the generation of SEI growth reduces the overall charge capacity of the battery cell by consuming some of the lithium that would otherwise be available for storing charge. This is a degradation mechanism known as lithium inventory loss (LLI). The properties and evolution of the solid-electrolyte interface layer fundamentally affect the overall performance of the lithium-ion battery cell. Reasons for this include: (i) the permeability of the solid-electrolyte interface layer to lithium ions can limit the rate and / or amount of lithium that can be stored at the anode; and (ii) the resistivity of the solid-electrolyte interface layer affects the rate of growth of the solid-electrolyte interface layer. Generally, the more conductive the SEI layer formed, the faster the further electrolyte decomposition, and therefore the faster the SEI layer grows. SEI layer growth increases lithium inventory loss (LLI). Due to LLI, less lithium is available to cycle between the positive and negative electrodes, which results in a reduction in the capacity of the lithium-ion battery cell.

[0017] Since the loss of lithium ions from the cathode and / or electrolyte reduces the overall capacity of a lithium-ion battery cell, attempts to reduce LLI or compensate for the LLI that occurs during a charge cycle are an active area of ​​research.

[0018] One approach is to "pre-lithiate" the anode material in situ. This involves designing a lithium-ion battery cell with an additional sacrificial lithium source, and typically involves performing a first charging cycle on the battery cell under non-standard operating conditions. During operation of the battery cell, this results in consumption of the "sacrificial" lithium source to provide SEI and maintain a minimum level of energy storage. One approach is to use lithium metal foil as an in-situ sacrificial lithium source, see US2021 / 0104737 A1. The document discloses a silicon dominant anode comprising a composite film comprising greater than 0% and less than about 90% silicon particles by weight, and greater than 0% and less than about 90% of one or more types of carbon phases by weight, wherein at least one of the one or more types of carbon phases is a substantially continuous phase that holds the composite film together so that the silicon particles are distributed throughout the composite material.

[0019] Another approach is to use "sacrificial electrolytes." These electrolytes include a higher molar concentration of lithium ions than the electrolytes best suited for normal cycling. During the first few cycles of a lithium-ion battery cell including such an electrolyte, the lithium ions and other electrolyte components degrade to form the SEI. Because a higher lithium concentration is used, the partial loss of lithium ions from the electrolyte to form the SEI results in the electrolyte still being able to function as a useful lithium-ion electrolyte.

[0020] An example of such a process is disclosed in US2021 / 0126250A1, where lithium or a lithium compound (such as lithium powder, lithium oxide, or lithium carbide powder) is added to the interior of a silicon-based anode during an early slurry stirring process or during later rolling, which can also be used for slurry-based materials.

[0021] However, even the use of sacrificial electrolytes typically results in partial loss of lithium from the cathode and overall suboptimal performance of the entire system.Another drawback is that achieving the required high concentrations of lithium salts imposes significant restrictions on what solvent / salt combinations can be employed.

[0022] Generally, designing battery cells so that they include a sacrificial source that is consumed (i) during the initial non-standard charging cycle or (ii) during normal use is disadvantageous because the battery cell must (i) include an additional sacrificial lithium source and (ii) typically operate under special initial SEI formation conditions in the first (first few) cycles. This imposes undesirable restrictions on the weight and size of the battery cell, the operating conditions of the battery cell, and / or the available electrolyte systems.

[0023] Another disadvantage of the in-situ pre-lithiation / SEI formation method is that the anode, which is primarily composed of silicon, swells significantly during charge and discharge, which, depending on the surface morphology, leads to significant ablation of the SEI during the first (first few) cycles. The ablated SEI material formed during the initial pre-lithiation / SEI formation method typically reduces the overall charge capacity, causes variability in the charge cycle and / or causes increased electrolyte decomposition and may cause the lithium-ion battery cell to short. Controlling the surface morphology to reduce the ablation of the SEI has been partially successful, but remains a challenge in improving the charge cycle life of lithium-ion battery cells.

[0024] It is an object of the present disclosure to provide a pre-lithiated silicon anode suitable for incorporation into a battery cell, thereby eliminating the need for an in-situ sacrificial lithium ion source in the final lithium ion battery cell.

[0025] Overview of the Disclosure

[0026] In view of the above discussion, a first aspect of the present disclosure is a method of manufacturing a lithium-ion battery cell (12), comprising the following steps:

[0027] (i) providing a silicon anode (6);

[0028] (ii) pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 1% to 100%;

[0029] (iii) providing a supply: a separator (2); an electrolyte; and a lithium ion cathode (3);

[0030] (iv) forming a lithium-ion battery cell from a pre-lithiated silicon anode (1), a separator (2) and a lithium-ion cathode (3), wherein the silicon anode (6) comprises a lithium storage material and a current collector, wherein the lithium storage material comprises between 70 wt.% and 100 wt.% silicon relative to the lithium storage material, preferably between 85 wt.% and 100 wt.% silicon, wherein the lithium storage material comprises a silicon material having a columnar morphology.

[0031] The subject method is superior to the in-situ pre-lithiation methods known in the prior art in that the pre-lithiation can be performed before assembling the final battery cell. Therefore, this method can advantageously eliminate the need for an in-situ sacrificial lithium ion source in the final lithium-ion battery cell.

[0032] Another aspect of the present disclosure is a lithium ion battery cell obtainable according to the foregoing aspects.Battery cells according to the present disclosure generally provide unexpected and excellent cycle life and capacity properties, which further confer the advantage of eliminating the need for an in-situ sacrificial lithium ion source in the final lithium ion battery cell.

[0033] Another aspect of the present disclosure is a lithium-ion battery cell (12) comprising:

[0034] A pre-lithiation silicon anode (3) having a pre-lithiation level of 1% to 100%;

[0035] Partition (4);

[0036] Electrolytes (5); and

[0037] The lithium ion cathode (6) is preferably a lithium ion cathode (6) having a lithiation level of 70% to 100%, more preferably 80% to 99% and even more preferably 90% to 98%.

[0038] The battery cells according to the present disclosure provide unexpected and excellent cycle life and capacity properties, which further afford the advantage of eliminating the need for an in-situ sacrificial lithium ion source in the final lithium ion battery cell.

[0039] In yet another aspect, the present disclosure relates to a battery comprising at least one lithium-ion battery cell according to any of the foregoing embodiments of any of the foregoing aspects. An advantage of such a battery is that the mass of such a battery can be lower than that of the prior art while still having the same nominal voltage and capacity. In the context of the present disclosure, a battery may comprise one or more lithium-ion battery cells.

[0040] A brief description of the attached figure

[0041] Figure 1 A method of manufacturing a lithium-ion battery cell according to the present disclosure is schematically depicted.

[0042] Figure 2A is a top-down scanning electron microscope image obtained from an anode including a silicon layer, where the silicon layer includes a plurality of columnar structures.

[0043] Figure 2B is a cross-sectional scanning electron microscope image obtained from an anode including a silicon layer, wherein the silicon layer includes a plurality of columnar structures.

[0044] Figure 3 3A, solid line). Example 3 (battery cell according to the present invention) exhibits a lower charge voltage and a higher discharge voltage than Comparative Example 3A. Therefore, Example 3 exhibits higher energy efficiency than Comparative Example 3A.

[0045] Figure 4 is a graph of capacity (Ah) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0046] Figure 5 is a graph of capacity retention (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0047] Figure 6 is a graph of specific capacity (Ah / g) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0048] Figure 7 is the area capacity (mAh / cm 2 ) is a graph of the number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and the comparative example (Example 3A).

[0049] Figure 8is a graph of cumulative specific capacity (Ah / g) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0050] Fig.9A is the specific energy (mWh / cm 2 ) is a graph of the number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and the comparative example (Example 3A).

[0051] Fig. 9B is a graph of energy efficiency (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0052] Fig.10 is a graph of (i) the number of charge cycles that can be performed until only 80% of the initial capacity of the full cell can be obtained; versus (ii) the lithium reserve divided by the lithium utilization. The lithium reserve is the lithium content in the silicon at the discharged state of the full cell, normalized to the mass of silicon in the silicon anode. The lithium utilization is the amount of lithium used during cycling, normalized to the mass of silicon in the silicon anode.

[0053] Definitions and abbreviations

[0054] Additive: A component present in the electrolyte in an amount of 0.01 wt.% to 10 wt.%.

[0055] Amorphous silicon: The term "amorphous silicon" herein is understood to include protocrystalline silicon, which is a definition of amorphous silicon that includes a portion of nanocrystalline silicon. This portion can be up to about 30% of the silicon layer. For ease of reference, the term amorphous silicon will be used herein to indicate that the silicon layer includes amorphous silicon, wherein the nanocrystalline region of the silicon layer can contain up to about 30% nanocrystalline silicon.

[0056] Anode: An electrode through which charge flows into an electronic device. In the context of an electrochemical perspective, anions (negatively charged ions) move toward the anode, and / or cations (positively charged ions) move away from the anode to balance the electrons leaving the electrode to the electronic device. When discharging a lithium-ion battery or galvanic cell, the anode is the negative terminal from which electrons flow out. When charging or recharging a lithium-ion battery, the anode becomes the positive terminal into which electrons flow from the electronic device.

[0057] Capacity: The capacity of a battery or battery cell is the amount of charge that such a device can deliver. Capacity is expressed in mAh or Ah and indicates the maximum constant current that a battery or battery cell can produce in one hour. For example, a battery with a capacity of 1Ah can provide 1A for 1 hour or 100mA for 10 hours.

[0058] Cathode: The electrode through which charge flows out of an electronic device. In the context of an electrochemical perspective, anions (negatively charged ions) move away from the anode and / or cations (positively charged ions) move toward the anode to balance the electrons entering the electrode from the electronic device. When discharging a lithium-ion battery or galvanic cell, the cathode is the positive terminal through which electrons flow. When charging or recharging a lithium-ion battery, the cathode becomes the negative terminal through which electrons flow out to the electronic device.

[0059] Battery Cell: An electrochemical device used to generate voltage or current from a chemical reaction or conversely where an applied current causes a chemical reaction.

[0060] Coulombic Efficiency (CE): The efficiency with which charge is transferred in a cell or battery. Coulombic efficiency can be defined as the amount of charge leaving a cell or battery during a discharge cycle divided by the amount of charge entering the cell or battery during the previous charge cycle.

[0061] DME: 1,2-dimethoxyethane.

[0062] DEC: diethyl carbonate.

[0063] Doping: The term "doping" is understood herein as the introduction of trace elements into a material to change the original electrical properties of the material or to improve the crystal structure of the silicon material.

[0064] EC: ethylene carbonate.

[0065] Electrolyte: A substance containing free ions that behaves as an ionically conductive medium. In the context of this disclosure, an electrolyte includes ions in solution.

[0066] FEC: Fluoroethylene carbonate.

[0067] Fluoroalkyl: An alkyl group in which at least one CH bond has been replaced by a CF bond.

[0068] Fluoroalkyl ether: In the context of this disclosure, the term refers to a fluoroalkyl ether having the general formula R 1 -OR 2 A fluorinated ether, wherein R 1 and R 2 At least one of R is independently selected from fluoroalkyl. The fluoroalkyl chain may be linear, cyclic or branched. The fluoroalkyl ether may be partially or fully fluorinated.1 and R 2 May be the same as or different from each other.

[0069] LiFSI: lithium bis(fluorosulfonyl)imide.

[0070] Perfluoroalkyl group: An alkyl group in which all CH bonds have been replaced by CF bonds.

[0071] Silicon anode: A silicon anode is an anode in which the majority of the mass is silicon, preferably at least 60 wt.%, more preferably at least 70 wt.%, and most preferably at least 70 wt.%.

[0072] Specific area capacity: This is the capacity per unit area of ​​the electrode or active material. The unit of specific area capacity is mAh / cm 2 .

[0073] Specific capacity: This is the capacity per unit mass. In this patent, mass specifically refers to the mass of silicon active material in the anode. Specific capacity can be expressed in units of mAh / g.

[0074] Solid Electrolyte Interface (SEI): A passivation layer that includes decomposed species resulting from the electrochemical decomposition of the electrolyte at the electrode / electrolyte phase boundary of the anode. This is typically formed during the first few cycles of a lithium-ion battery or cell.

[0075] TTE: 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0076] Detailed Description of the Invention

[0077] Method for manufacturing lithium-ion battery cell

[0078] The present disclosure relates to a method for manufacturing a lithium-ion battery cell (12), comprising the following steps:

[0079] (i) providing a silicon anode (6);

[0080] (ii) pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 1% to 100%;

[0081] (iii) providing a supply: a separator (2); an electrolyte; and a lithium ion cathode (3);

[0082] (iv) forming a lithium-ion battery cell from a pre-lithiated silicon anode (1), a separator (2) and a lithium-ion cathode (3),

[0083] Wherein, the silicon anode (6) comprises:

[0084] - a lithium storage material, wherein the lithium storage material comprises between 70 wt.% and 100 wt.% silicon relative to the lithium storage material, preferably wherein the lithium storage material comprises between 85 wt.% and 100 wt.% silicon relative to the lithium storage material; wherein the lithium storage material comprises a silicon material having a columnar morphology; and

[0085] -Current collector.

[0086] This method is superior to the in-situ pre-lithiation methods known in the prior art in that the pre-lithiation can be performed before assembling the final battery cell. In addition, the specific choice of silicon material with columnar morphology allows for enhanced performance and longer cycle life.

[0087] Therefore, the method eliminates the need for an in-situ sacrificial lithium ion source in the final lithium ion battery cell.

[0088] Preferably, the method comprises the following additional steps:

[0089] - Cleaning the pre-lithiated silicon anode (1).

[0090] This additional step can advantageously remove any ablated SEI from the silicon anode surface that is formed during the pre-lithiation step of connecting the silicon anode and sacrificial lithium ion cathode of the first intermediate battery cell to an external circuit. Without being limited by theory, it is believed that the presence of ablated SEI material reduces the cycle life of the lithium ion battery cell by degrading the electrolyte.

[0091] Silicon Anode

[0092] The method according to the present disclosure comprises providing a silicon anode (6). The silicon anode according to the present disclosure comprises:

[0093] - a lithium storage material, wherein the lithium storage material comprises between 70 wt.% and 100 wt.% silicon relative to the lithium storage material, preferably wherein the lithium storage material comprises between 85 wt.% and 100 wt.% silicon relative to the lithium storage material, preferably wherein the lithium storage material comprises between 85 wt.% and 100 wt.% silicon relative to the lithium storage material; the lithium storage material comprises a silicon material having a columnar morphology, and

[0094] -Current collector.

[0095] Preferably, the silicon anode according to the present disclosure includes an interstitial adhesion layer.

[0096] Current Collector

[0097] Preferably, the current collector materials according to the present disclosure each have a thickness of 1 μm to 100 μm, preferably 5 μm or 10 μm to 50 μm, more preferably 10 μm to 15 μm, or about 10 μm or 12 μm.

[0098] Advantageously, the current collector material according to the present disclosure may include copper, tin, chromium, nickel, titanium, stainless steel or silver, or alloys thereof, more preferably copper or nickel, or alloys thereof, most preferably copper.

[0099] The current collector material includes a sheet material produced by cold rolling or electroplating, and may also include an alloy of copper or titanium with elements such as magnesium, zinc, tin, phosphorus and / or silver. It may be smooth, rough or textured, with a tensile strength preferably of 150MPa to 600MPa, and may include a passivation layer deposited on the copper foil to protect the copper foil from oxidation in the air. The sheet material produced by cold rolling or electroplating may have certain defects, such as rolling lines, potential strains, impurities and native oxides, which may affect the quality of the active material layer. Therefore, the current collector material may be surface treated. For example, by attaching the nodules of the current collector material or other metals to the surface of the current collector material, such as by electroplating, the roughness of the foil may be increased to varying degrees. Other surface treatment techniques known in the art include annealing, knurling, etching, liquefaction, physical polishing and electropolishing, and are used to improve the morphology of the current collector material before depositing the active material.

[0100] Preferably, the current collector material according to the present disclosure comprises a metal, a metal alloy and / or a metal salt and / or an oxide. The metal, metal alloy and / or metal salt and / or oxide according to the present disclosure is advantageously selected from aluminum, copper, nickel, tin, tin, indium and zinc, preferably nickel, ZnO or SnO2, most preferably ZnO; preferably, wherein the current collector comprises a copper or nickel core layer, more preferably a core layer doped with an oxide or fluoride of zinc, aluminum, tin or indium. Preferably, the metal, metal alloy and / or metal salt and / or oxide or core layer is in a layer having a thickness of 0.1 nm to 5 nm, more preferably 1 nm to 2 nm. Preferably, the current collector comprising copper or nickel according to the present disclosure comprises nickel, ZnO or SnO2.

[0101] Optional interstitial adhesion layer

[0102] The current applicant's pending international patent application WO2021029769 discloses that an adhesion layer including a metal, metal alloy and / or metal salt and / or oxide attached to a current collector material can advantageously increase the adhesion of a silicon material to the current collector material of a composite electrode. This interstitial adhesion layer is not required. According to the present disclosure, the current collector material comprising a metal, metal alloy and / or metal salt and / or oxide adhesion layer preferably includes an adhesion layer. However, the adhesion layer can advantageously increase the adhesion between the silicon material and the current collector material because different silicon composites are formed at the interface between the current collector material and silicon. This adhesion layer preferably includes nickel, zinc or tin, such as ZnO or SnO2. The adhesion layer can be formed by coating or depositing metals, metal alloys and / or metal salts and / or oxides on the current collector material. Preferably, the adhesion layer is located in a layer having a thickness of 0.1nm to 5nm, more preferably 1nm to 2nm.

[0103] Lithium storage materials

[0104] In the context of the present disclosure, the lithium storage material comprises between 70 wt.% and 100 wt.% silicon. Preferably, the lithium storage material in the context of the present disclosure comprises between 85 wt.% and 100 wt.% silicon relative to the lithium storage material.

[0105] Preferably, the lithium storage material includes 75.0wt.% to 100.0wt.% silicon, preferably includes 80.0wt.% to 100.0wt.% silicon, more preferably includes 85.0wt.% to 100.0wt.% silicon, still more preferably 90.0wt.% to 100.0wt.% silicon, more preferably 92.0wt.% to 99.8wt.% silicon, even more preferably 94.0wt.% to 99.6wt.% silicon, still more preferably 96.0wt.% to 99.4wt.% silicon, still more preferably 98.0wt.% to 99.2wt.% silicon, and most preferably 99.0wt.% to 99.1wt.% silicon.

[0106] Preferably, the material of the lithium storage material includes amorphous silicon and a nanocrystalline silicon alloy. In some embodiments, the lithium storage material may be present in the electrode layer as a nanocrystalline phase. In addition, the lithium storage material may include a mixture of an amorphous material and a nanocrystalline phase. For example, a mixture of amorphous silicon and nanocrystalline silicon, or a mixture of amorphous silicon and a nanocrystalline silicon alloy, or a mixture of silicon and a silicon-based alloy that is mainly in an amorphous state includes a portion (up to about 30%) of the mixture that is in a nanocrystalline state.

[0107] The lithium storage material layer according to the present disclosure may advantageously include silicon oxide.The silicon layer according to the present disclosure may be positioned on the current collector layer in various configurations.

[0108] The lithium storage material includes a silicon material having a columnar morphology.

[0109] According to the present disclosure, amorphous silicon pillars preferably extend in a vertical direction from the anode surface (ie, the interface between the anode layer and the electrolyte layer), wherein a plurality of silicon pillars are arranged adjacent to each other while being separated by the interface extending perpendicular to the anode surface.

[0110] Preferably, the silicon material in the lithium storage material comprises a plurality of columnar structures on the current collector. The lithium storage material is present on the current collector layer.

[0111] The lithium storage material according to the present disclosure is preferably attached to the current collector layer as a layer comprising a plurality of adjacent pillars having a diameter of 0.5 μm to 100 μm, either directly or through attachment to an interstitial adhesion layer.

[0112] Preferably, the columns have a diameter of 1 to 75 μm, more preferably 2 to 50 μm, even more preferably 3 to 25 μm, still more preferably 4 to 20 μm, even more preferably 5 to 15 μm, still more preferably 6 to 12 μm, most preferably 8 to 10 μm.

[0113] Preferably, the pillars have an average diameter of 1 μm to 75 μm, more preferably 2 μm to 50 μm, even more preferably 3 μm to 25 μm, still more preferably 4 μm to 20 μm, even more preferably 5 μm to 15 μm, still more preferably 6 μm to 12 μm, most preferably 8 μm to 10 μm.

[0114] Preferably, the pillars extend primarily in a vertical direction from the current collector layer surface, wherein adjacent pillars are separated by pillar boundaries extending in the vertical direction. This can be determined by cross-sectional electron microscopy.

[0115] Preferably, the method is wherein the lithium storage material comprises a silicon material having a nanoscale structure on the surface, and preferably the nanoscale has a columnar morphology or a similar structure.

[0116] The silicon layer can be placed on the nanowire template, which is attached to a substrate, such as a current collector layer or an adhesion layer. The term "nanowire" herein is understood to be a branched or non-branched linear structure having at least one dimension and a length of up to about 1 μm. Nanowires are conductive materials, including, for example, carbon, metals or metal silicides, such as nickel silicide, copper silicide, silver silicide, chromium silicide, cobalt silicide, aluminum silicide, zinc silicide, titanium silicide or iron silicide, preferably including at least one nickel silicide phase containing Ni2Si, NiSi or NiSi2. The nanowire can be the same material as the current collector, such as nickel, copper or titanium. Alternatively, the nanowire can be a material and layer separated from the current collector material (e.g., a copper current collector coated with a nickel layer). One or more layers of active material (such as silicon) can be deposited on the nanowire by, for example, PVD, CVD or PECVD. The silicon layer can include carbon, copper, sulfides, metal oxides, fluorinated compounds, polymers or lithium phosphorus oxynitrides. The silicon layer may be coated with a layer comprising carbon, copper, sulfides, metal oxides, fluorinated compounds, polymers or lithium phosphorus oxynitride, preferably a carbon layer having a thickness of 1 nm to 5 μm, preferably a thickness of 10 nm to 1 μm.

[0117] Preferably, the method is one in which the silicon anode (6) comprises a layer of lithium storage material.

[0118] Preferably, according to the present disclosure, the lithium storage material layer has a thickness of 0.1 μm to 1000 μm, preferably 0.5 μm to 500 μm, more preferably 1 μm to 100 μm or 200 μm, even more preferably 1 μm to 30 μm or 50 μm, still more preferably 3 μm to 20 μm, still more preferably 5 μm to 15 μm, and most preferably 6 μm to 10 μm. Alternatively, according to the present disclosure, the lithium storage material layer has a mass loading of preferably 0.1 mg / cm 2 Up to 4.0mg / cm 2 , more preferably 0.5 mg / cm 2 or 0.8mg / cm 2 Up to 2.0mg / cm 2 Up to 2.5 mg / cm 2 , or 2.5mg / cm 2 Up to 3.5mg / cm 2 or 4.0mg / cm 2 , most preferably 1.0 mg / cm 2 Up to 2.0mg / cm 2 The mass loading relates to the mass loading of a layer of lithium storage material present on one side of the current collector layer.

[0119] Advantageously, the lithium storage material layer according to the present disclosure has a porosity of 0% to 50%, more preferably 1%, 2%, 5% or 10% to 50%.

[0120] Preferably, the lithium storage material layer according to the present disclosure has a porosity of 0% to 80%, preferably 5%-60%, even more preferably 10%-40%, as determined by the BJH method of ISO 15901-2:2006.

[0121] Preferably, the average pore size of the lithium storage material layer is in the range of 0.5 nm to 40 nm, preferably in the range of 1 nm to 20 nm.

[0122] The porosity and (average) pore size according to the present disclosure are preferably determined using nitrogen according to the method specified by the ISO (International Organization for Standardization) standard: ISO 15901-2:2006 "Pore size distribution and porosity of solid materials by mercury porosimetry and gas adsorption—Part 2: Analysis of mesopores and macropores by gas adsorption". In short, the N2 adsorption isotherm is measured at about -196°C (liquid nitrogen temperature). The pore size and pore volume can be determined according to the calculation method of Barrett-Joyner-Halenda (Barrett, EP; Joyner, LG; Halenda, PP (1951), "The Determination of Pore Volume and Area Distributions in Porous Substances. I. Computations from Nitrogen Isotherms", Journal of the American Chemical Society, 73(1):373-380). The specific surface area can be determined from the same isotherm according to the Brunauer-Emmett-Teller calculation method (Brunauer, S.; Emmett, PH; Teller, E. (1938), "Adsorption of Gases in Multimolecular Layers", Journal of the American Chemical Society, 60 (2): 309-319). Both calculation methods are well known in the art. A simple experimental test method for determining the isotherm can be described as follows: The test sample is dried at high temperature and in an inert atmosphere. The sample is then dried and placed in a measuring instrument. Next, the sample is placed under vacuum and cooled using liquid nitrogen. During the recording of the isotherm, the sample is kept at liquid nitrogen temperature.

[0123] The lithium storage material layer according to the present disclosure preferably has an amorphous structure in which nanocrystalline regions are present. More preferably, the lithium storage material layer and / or the lithium storage material column comprises up to 30% nanocrystalline silicon. According to an embodiment, the lithium storage material layer and / or the lithium storage material column advantageously comprises an n-type or p-type dopant to obtain a silicon layer having n-type conductivity or p-type conductivity, respectively.

[0124] Advantageously, the lithium storage material column may also include a silicon alloy, wherein the silicon alloy is preferably selected from the group including Si-C and / or Si-N. Preferably, the composite material according to the present disclosure includes: carbon or an alloy containing carbon or silicon. The silicon alloy may be an additive or substitute for amorphous silicon. Therefore, according to aspects of the present disclosure, the material of the column includes at least one material selected from amorphous silicon and an amorphous silicon alloy.

[0125] Partition

[0126] The method according to the invention comprises providing a separator.

[0127] Separators suitable for use in the present disclosure are known to those skilled in the art and are commercially available.

[0128] The separator is present to prevent a short circuit from forming between the cathode and anode while still allowing ions to flow between the two electrodes.

[0129] The separator may be appropriately selected from: (i) glass fibers; (ii) porous polymer films with or without ceramic coatings, such as polyethylene or polypropylene-based materials, or (iii) composite materials (e.g., porous films of inorganic particles and binders). An exemplary polymer separator is K1640 polyethylene (PE) film. Another exemplary polymer separator is 2500 polypropylene film. Another exemplary polymer separator is 3501 surfactant coated polypropylene film.

[0130] Another group of exemplary porous polymer membranes with ceramic coatings are PE and PP separators available from Gelon. An example of such a separator is the Gelon 16 μm thick PE battery separator, which comprises a 12 μm thick polyethylene polymer film coated on both sides with a 2 μm thick ceramic alumina layer to provide a separator with a porosity of 38%.

[0131] The separator may optionally be impregnated with electrolyte.

[0132] Electrolytes

[0133] Electrolytes suitable for use in the present disclosure are known to those skilled in the art and are commercially available. Suitable electrolytes include a lithium salt and a solvent.

[0134] Lithium salts

[0135] The first electrolyte and the second electrolyte have a 0.5M (mol / dm 3 ) to a lithium salt concentration of 2M.

[0136] Lithium salts or combinations of lithium salts are involved in the charging and discharging process of the battery cell.

[0137] Preferably, the lithium salt includes: LiAsF6, Li2SO4, LiBF4, LiBr, LiCF3SO3, LiCl, LiClO4, LiI, LiNO2, LiNO3, LiSCN, 2-trifluoromethyl-4,5-dicyanoimidazole lithium (CAS: 761441-54-7), (fluorosulfonyl) (trifluoromethylsulfonyl) imide lithium (LiFTFSI), bis (fluorosulfonyl) imide lithium (LiFSI); bis (oxalate) borate lithium (LiBOB), bis (pentafluoroethanesulfonyl) imide lithium (LiBETI), bis (trifluoromethanesulfonyl) imide lithium (LiTFSI), difluoro (oxalate) borate lithium (LiDFOB CAS: 409071-16-5), trifluoromethanesulfonate lithium (LiTf), LiPF6 or any combination thereof.

[0138] More preferably, the electrolyte comprises 9 wt.% to 29 wt.% of a lithium salt, relative to the electrolyte, selected from the group consisting of LiAsF6, Li2SO4, LiBF4, LiBr, LiCF3SO3, LiCl, LiClO4, LiI, LiNO2, LiNO3, LiSCN, 2-trifluoromethyl-4,5-dicyanoimidazole lithium (CAS: 761441-54-7), (fluorosulfonyl)(trifluoromethylsulfonyl)imide lithium (LiFTFSI), bis(fluorosulfonyl)imide lithium (LiFSI); bis(oxalate)borate lithium (LiBOB), bis(pentafluoroethanesulfonyl)imide lithium (LiBETI), bis(trifluoromethanesulfonyl)imide lithium (LiTFSI), difluoro(oxalate)borate lithium (LiDFOB CAS: 409071-16-5), trifluoromethanesulfonate lithium (LiTf), LiPF6 or any combination thereof.

[0139] Most preferably, the lithium salt consists essentially of lithium bis(fluorosulfonyl)imide.

[0140] Solvents

[0141] The electrolyte comprises a solvent. The solvent is advantageously selected so that the lithium salt has a solubility of at least 0.3 M (mol / dm 3 ).

[0142] Preferably, the non-aqueous solvent is selected such that the lithium salt has a solubility in the selected solvent of at least 4 M at 25°C and 1 atm, more preferably at least 5 M at 25°C and 1 atm.

[0143] Without being limited by theory, it is believed that the solvent molecules in the electrolyte according to the present disclosure are statistically most likely to be tightly associated with the lithium ion salt to form aggregates. It is further believed that these solvent-lithium salt aggregates are suspended in the continuous phase of the diluent.

[0144] Preferably, the non-aqueous solvent is selected from a non-aqueous solvent comprising at least one of the following components: (i) esters, (ii) sulfur-containing solvents, (iii) phosphorus-containing solvents, (iv) ethers, (v) nitriles, or (vi) any combination thereof.

[0145] Ester solvent

[0146] Preferably, the ester is selected from: diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dimethyl carbonate (DMC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), methyl 2,2,2,-trifluoroethyl carbonate (MFEC), propylene carbonate (PC), trifluoroethylene carbonate (TFEC), trifluoropropylene carbonate (TFPC), 2,2,2,-trifluoroethyl trifluoroacetate, ethyl 2,2,2-trifluoroacetate, alkyl carboxylate (such as ethyl acetate), ethyl propionate, ethyl trifluoroacetate, methyl butyrate or any combination thereof.

[0147] More preferably, the ester is selected from: 2,2,2,-trifluoroethyl trifluoroacetate, 2,2,2-ethyl trifluoroacetate, ethyl acetate, ethyl acetate, ethyl propionate, ethyl trifluoroacetate, methyl butyrate and / or any combination thereof.

[0148] Sulfur-containing solvents

[0149] Preferably, the sulfur-containing solvent is selected from sulfone solvents, sulfoxide solvents or any combination thereof. More preferably, the sulfur-containing solvent is selected from dimethyl sulfone, dimethyl sulfone, ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS, sulfolane), dimethyl sulfoxide, ethyl methyl sulfoxide, ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS, sulfolane), dimethyl sulfoxide, ethyl methyl sulfoxide or any combination thereof.

[0150] Phosphorus-containing solvents

[0151] Preferably, the phosphorus-containing solvent is selected from organophosphorus compounds (such as organophosphates, phosphites, phosphonates, phosphoramides), phosphazenes (organic or inorganic) or any combination thereof.These phosphorus-containing solvents are typically flame retardants.

[0152] More preferably, the phosphorus-containing solvent is selected from: bis(2,2,2-trifluoroethyl)methyl phosphate, tributyl phosphate, triethyl phosphate (TEPa), trimethyl phosphate (TMPa), triphenyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, trimethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphite, dimethyl methyl phosphonate; diethyl ethyl phosphonate, diethyl phenyl phosphonate, bis(2,2,2-trifluoroethyl) methyl phosphonate, hexamethylphosphoramide, hexamethoxyphosphazene (CAS: 957-13-1), hexamethoxycyclotriphosphazene (CAS: 6607-30-3), hexafluorophosphazene (CAS: 15599-91-4) or any combination thereof.

[0153] Ether solvent

[0154] Preferably, the ether solvent is selected from: 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), 1,3-dioxolane (DOL), allyl ether or any combination thereof.

[0155] Nitrile solvents

[0156] Preferably, the nitrile solvent is selected from: acetonitrile, propionitrile, succinonitrile, adiponitrile (CAS: 111-69-3) or any combination thereof.

[0157] The electrolyte preferably includes a non-aqueous solvent selected from the following items: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), difluoroethylene carbonate (DFEC), trifluoroethylene carbonate (TFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2,-trifluoroethyl carbonate (MFEC), ethyl acetate, ethyl propionate, methyl butyrate; ethyl trifluoroacetate, ethyl 2,2,2-trifluoroethyl acetate, 2,2,2-trifluoroethyl trifluoroacetate, dimethyl sulfone (DMS), ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS), dimethyl sulfoxide, ethyl methyl sulfoxide, trimethyl phosphate (TMPa), triethyl phosphate (TEPa), trisphosphate ester, triphenyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, trimethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphite, dimethyl methyl phosphonate, diethyl ethyl phosphonate, diethyl phenyl phosphonate, bis(2,2,2-trifluoroethyl) methyl phosphonate, hexamethylphosphoramide, hexamethoxyphosphazene, hexamethoxycyclotriphosphazene, hexafluorophosphazene, 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (diglyme, DEGDME), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), 1,3-dioxolane (DOL), allyl ether, acetonitrile, propionitrile, succinonitrile, adiponitrile (CAS: 111-69-3) or any combination thereof.

[0158] Even more preferably, the non-aqueous solvent is selected from the group consisting of: ethyl acetate, ethyl propionate, methyl butyrate, ethyl trifluoroacetate, ethyl 2,2,2-trifluoroacetate, 2,2,2-trifluoroethyl trifluoroacetate; dimethyl sulfone (DMS), ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS), dimethyl sulfoxide, ethyl methyl sulfoxide, trimethyl phosphate (TMPa), triethyl phosphate (TEPa), tributyl phosphate, triphenyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, trimethyl phosphite, triphenyl phosphite, tris(2 ,2,2-trifluoroethyl)phosphite, dimethyl methyl phosphonate, diethyl ethyl phosphonate, diethyl phenyl phosphonate, bis(2,2,2-trifluoroethyl)methyl phosphonate, hexamethylphosphoramide, hexamethoxyphosphazene (cyclo-tris(dimethoxyphosphazene), hexamethoxycyclotriphosphazene), hexafluorophosphazene (hexafluorocyclotriphosphazene), 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (DEGDME, or diethylene glycol dimethyl ether), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), 1,3-dioxolane (DOL), allyl ether, acetonitrile, propionitrile, or any combination thereof.

[0159] Preferably, the solvent is a mixture of FEC and DEC. Most preferably, the solvent is a 3:7 (volume ratio) mixture of FEC:DEC.

[0160] Preferred electrolyte composition ratio

[0161] Preferably, the electrolyte according to the present disclosure has a molecular weight of 0.01 M (mole / dm 3 ) to 10 M, more preferably 0.1 M to 5 M, even more preferably 0.2 M to 3 M, still more preferably 0.5 M to 2 M, and most preferably 1 M lithium salt concentration.

[0162] Preferred additives

[0163] Preferably, the electrolyte according to the present disclosure further comprises an additive. The additive has a composition different from: (i) a lithium salt; (ii) a solvent; and (iii) a diluent. Optionally, the additive is a flame retardant.

[0164] Preferably, the additives include: 4-fluoro-1,3-dioxolane-2-one (FEC, CAS: 114435-02-8), 1,3-dioxol-2-one (VC, vinylene carbonate, CAS: 872-36-6), 1,4-dicyanobutane (adiponitrile, CAS: 111-69-3), lithium difluorophosphate (LiDFP), 4,5-dimethylene-1,3-dioxolane-2-one, 1,3,2-dioxathiolane-2-oxide (CAS: 3741-38-6) 1,3,2-dioxathiolane-2,2-dioxide (CAS: 1072-36-6). -53-3), 1,3,2-dioxathiacyclohexane-2,2-dioxide (DTD, CAS: 1072-53-3), 3-methyl-1,4,2-dioxazol-5-one (CAS: 854849-14-2), tris(2,2,2-trifluoroethyl)phosphite (TTFEPi, CAS: 370-69-4), 1,3,2-dioxathiacyclohexane-2-oxide (CAS: 4176-55-0), 1-methylsulfonylethylene (CAS: 3680-02-2), 1-vinylsulfonylethylene (CAS: 77-77--0) or any combination thereof.

[0165] Divider

[0166] In any aspect of the present disclosure, a separator is a material that ensures that there is no physical, electrical or ionic connection between the layers it separates.

[0167] Separators suitable for use in the present disclosure are known to those skilled in the art and are commercially available. An example of a suitable separator is a polypropylene sheet.

[0168] (Non-sacrificial) Li-ion cathode

[0169] The method according to the invention comprises providing a (non-sacrificial) lithium ion cathode (3).

[0170] Cathodes suitable for use in the present disclosure are known to those skilled in the art and are commercially available.

[0171] Preferably, the cathode or the positive electrode or the material they consist essentially of is selected from:

[0172] Carbon / sulfur composites or air electrodes, in particular carbon-based electrodes, comprising graphitic carbon and optionally a metal catalyst such as Ir, Ru, Pt, Ag or Ag / Pd; carbon monofluoride; CuO (copper oxide); Cr2O5; Cr3O8; iron disulfide; Li2M 2 SiO4(M 2 =Mn, Fe or Co), Li2M 2 SO4(M 2 =Mn, Fe or Co), LiM2SO4 m F (M2 = Fe, Mn or Co), Li 2-x (Fe 1-y Mn y )P2O7(0≤x≤1;0≤y≤1), Li3V 2-x M1 x (PO4)3(M1=Cr, Co, Fe, Mg, Y, Ti, Nb or Ce; 0≤x≤1); Li 4- x M x Ti5O 12 (M=Mg, Al, Ba, Sr or Ta; 0≤x≤1); LiCoO2; LiFePO4(LFP); LiMC1 x MC 2 1-x O2 (MC1 and MC2 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al; 0≤x≤1); LiMC1 x MC2 1-x PO4(MC1 or MC2=Fe, Mn, Ni, Co, Cr or Ti; 0≤x≤1); LiMC1 x MC2 y MC3 1-x-yO2 (MC1, MC2 and MC3 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al respectively; 0≤x≤1; 0≤y≤1, 0≤x+y≤1); LiMn2O4 (LMO); LiMn 2-y X y O4(X=Cr, Al or Fe, 0≤y≤1); LiNi 0.5 Mn 1.5 O4 spinel; LiNi 0.5-y X y Mn 1.5 O4 (X=Fe, Cr, Zn, Al, Mg, Ga, V or Cu; 0≤y<0.5); LiNi 0.8 Co 0.15 Al 0.05 O2(NCA);LiNi x Mn y Co Z O2 (NMC, x+y+z=1), Li-rich Li 1+w Ni x Mn y Co Z O2(x+y+z+w=1,0≤w≤0.25); LiV3O8; LiVPO4F; MnO2; thionyl chloride; V2O5; V6O1; xLi2MnO3·(1-x)LiM 1 y M 2 M 3 1-y-z O2, where M 1 、M 2 and M 3 Respectively Mn, Ni, Co, Cr, Fe or a mixture thereof; and wherein x=0.3-0.5; y≤0.5; z≤0.5.

[0173] In a preferred embodiment, the cathode is a lithium conversion compound such as Li2O2, Li2O, Li2S or LiF. More preferably, the cathode comprises LiNi X Mn Y Co Z O2, where x ≥ 0.6 (NMC) or LiNi x Mg y Ti 1-x-y O2, where 0.9≤x<1(NMT; e.g., LiNi 0.96 Mg 0.02 Ti 0.02 O2).

[0174] In a particularly preferred embodiment, the cathode is selected from one or more high voltage cathodes, which means a cathode that can be operated at 4.3V to 4.6V.

[0175] Solid electrolyte interface layer

[0176] This may be any solid electrolyte interface layer formed by charging and discharging the silicon anode (6) in the presence of a lithium salt containing electrolyte and a sacrificial cathode (4).

[0177] Step of pre-lithiating the silicon anode to form a pre-lithiated silicon anode

[0178] The method of the present disclosure involves the step of pre-lithiating a silicon anode (6) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 20% to 100%.

[0179] The pre-lithiation level is defined as: [(amount of lithium contained in the silicon anode) / (theoretical maximum amount of lithium that can be contained in the silicon anode)]×100.

[0180] Preferably, the silicon anode (6) is pre-lithiated to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 2% to 80%, preferably 3% to 60%, even more preferably 5% to 40%, still more preferably 10% to 30% and most preferably 15% to 20%.

[0181] Preferably, the step of pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 20% to 100% is selected from one of the following methods:

[0182] - electrochemically pre-lithiating the silicon anode (6) using a sacrificial lithium ion cathode (4);

[0183] - treating the silicon anode (6) with a sacrificial electrolyte salt; or

[0184] - Physical deposition of lithium on the silicon anode (6).

[0185] Electrochemical pre-lithiation of a silicon anode (6) using a sacrificial lithium ion cathode (4)

[0186] The method according to the present invention optionally includes pre-lithiating the silicon anode (6) by electrochemically pre-lithiating the silicon anode (6) with a sacrificial lithium ion cathode (4) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 20% to 100%.

[0187] Sacrificial lithium-ion cathode

[0188] Cathodes suitable for use as sacrificial cathodes in the present disclosure are known to those skilled in the art and are commercially available.

[0189] Preferably, the cathode or the positive electrode or the material they consist essentially of is selected from:

[0190] Carbon / sulfur composites or air electrodes, in particular carbon-based electrodes, comprising graphitic carbon and optionally a metal catalyst such as Ir, Ru, Pt, Ag or Ag / Pd; carbon monofluoride; CuO (copper oxide); Cr2O5; Cr3O8; iron disulfide; Li2M 2 SiO4(M 2 =Mn, Fe or Co), Li2M 2 SO4(M 2 =Mn, Fe or Co), LiM2SO4 m F (M2 = Fe, Mn or Co), Li 2-x (Fe 1-y Mn y )P2O7(0≤x≤1;0≤y≤1), Li3V 2-x M1 x (PO4)3(M1=Cr, Co, Fe, Mg, Y, Ti, Nb or Ce; 0≤x≤1); Li 4- x M x Ti5O 12 (M=Mg, Al, Ba, Sr or Ta; 0≤x≤1); LiCoO2; LiFePO4(LFP); LiMC1 x MC 2 1-x O2 (MC1 and MC2 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al; 0≤x≤1); LiMC1 x MC2 1-x PO4(MC1 or MC2=Fe, Mn, Ni, Co, Cr or Ti; 0≤x≤1); LiMC1 x MC2 y MC3 1-x-y O2 (MC1, MC2 and MC3 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al respectively; 0≤x≤1; 0≤y≤1, 0≤x+y≤1); LiMn2O4 (LMO); LiMn 2-y X y O4(X=Cr, Al or Fe, 0≤y≤1); LiNi 0.5 Mn 1.5 O4 spinel; LiNi 0.5-y X y Mn 1.5 O4 (X=Fe, Cr, Zn, Al, Mg, Ga, V or Cu; 0≤y<0.5); LiNi 0.8 Co 0.15 Al 0.05 O2(NCA);LiNi x Mny Co Z O2 (NMC, x+y+z=1), Li-rich Li 1+w Ni x Mn y Co Z O2(x+y+z+w=1,0≤w≤0.25); LiV3O8; LiVPO4F; MnO2; thionyl chloride; V2O5; V6O1; xLi2MnO3·(1-x)LiM 1 y M 2 M 3 1-y-z O2, where M 1 、M 2 and M 3 Mn, Ni, Co, Cr, Fe or a mixture thereof; and wherein x=0.3-0.5; y≤0.5; z≤0.5; or LiCl.

[0191] In a preferred embodiment, the cathode is a lithium conversion compound such as Li2O2, Li2O, Li2S or LiF. More preferably, the cathode comprises LiNi X Mn Y Co Z O2, where x ≥ 0.6 (NMC) or LiNi x Mg y Ti 1-x-y O2, where 0.9≤x<1(NMT; e.g., LiNi 0.96 Mg 0.02 Ti 0.02 O2).

[0192] In a particularly preferred embodiment, the cathode is selected from one or more high voltage cathodes, which means a cathode that can be operated at 4.3V to 4.6V.

[0193] Treatment of silicon anodes with sacrificial electrolyte salts (6)

[0194] This can optionally be achieved by contacting the silicon anode (6) with a reactive lithium ion salt, preferably an organometallic lithium salt.

[0195] More preferably, the silicon anode (6) is contacted with the organometallic lithium salt under a dry and inert atmosphere (such as oxygen-free argon or nitrogen). Even more preferably, the organometallic salt is selected from methyllithium, n-butyllithium, sec-butyllithium, isopropyllithium, tert-butyllithium, phenyllithium or any combination thereof. Most preferably, the organometallic salt is n-butyllithium.

[0196] Preferably, the organometallic lithium salt is provided as a solution in an alkane solvent, an ether solvent or a combination thereof, more preferably in an alkane solvent.

[0197] Physical deposition of lithium onto silicon anodes

[0198] This can optionally be achieved by sputtering lithium onto the silicon anode (6) or by contacting the silicon anode (6) with a lithium foil.

[0199] Production by process

[0200] Another aspect of the present disclosure relates to a lithium-ion battery cell obtainable by the method as described above. The lithium-ion battery cell according to this aspect of the present disclosure surprisingly has excellent cycle life and capacity.

[0201] Lithium-ion battery cells

[0202] Another aspect of the present disclosure relates to a lithium-ion battery cell (12) comprising:

[0203] - a pre-lithiated silicon anode (3) having a pre-lithiation level of 1% to 100%,

[0204] - a partition (4);

[0205] - electrolyte (5); and

[0206] - a lithium ion cathode (6).

[0207] Preferably, the lithium ion cathode (6) has a lithiation level of 70% to 100%, more preferably 80% to 99%, and again more preferably 90% to 98%, such as a lithium ion cathode (6) with a lithiation level of 90% to 100%. More preferably, the lithium ion cathode (6) has a lithiation level of 91% to 99%, more preferably 92% to 98%, even more preferably 93% to 97%, still more preferably 94% to 96% and most preferably 95%.

[0208] In embodiments, the lithium ion battery cell according to the present invention has advantageous properties, particularly high capacity, high capacity retention, high specific capacity, and long cycle life.

[0209] Without being limited by theory, it is believed that such cells have higher electrochemically available lithium ion storage in (i) the anode and (ii) the cathode than comparable cells.

[0210] The pre-lithiated silicon anode (3) having a pre-lithiation level of 1% to 100% may be prepared as described in any of the preceding aspects of the present disclosure.

[0211] Preferably, the pre-lithiated silicon anode (3) has a pre-lithiation level of 2 to 80%, preferably 3 to 60%, even more preferably 5 to 40%, still more preferably 10 to 30% and most preferably 15 to 20%.

[0212] The separator (4) is as described in the above aspect. The electrolyte (5) is as described in the above aspect.

[0213] Lithium-ion cathode

[0214] A lithium ion battery cell according to this aspect of the invention comprises a lithium ion cathode (6).

[0215] Preferably, the lithium ion cathode (6) has a lithiation level of 70% to 100%, more preferably 80% to 99%, and again more preferably 90% to 98%, such as a lithium ion cathode (6) having a lithiation level of 90% to 100%.

[0216] The lithiation level is defined as: [(the amount of lithium actually present in the cathode) / (the theoretical maximum amount of lithium that the cathode can contain)]×100.

[0217] A lithium ion cathode (6) having a lithiation level of 70% to 100%, more preferably 80% to 99%, and again more preferably 90% to 98% (e.g., a lithium ion cathode (6) having a lithiation level of 90% to 100%) can be prepared as described in any of the foregoing aspects of the present disclosure. Preferably, the lithium ion cathode (6) has a lithiation level of 91% to 99%, more preferably 92% to 98%, even more preferably 93% to 97%, still more preferably 94% to 96% and most preferably 95%.

[0218] Preferably, the lithium ion cathode (6) is selected from: a carbon / sulfur composite or an air electrode, in particular a carbon-based electrode comprising graphitic carbon and optionally a metal catalyst such as Ir, Ru, Pt, Ag or Ag / Pd; carbon monofluoride; CuO (copper oxide); Cr2O5; Cr3O8; iron disulfide; Li2M 2 SiO4(M 2 =Mn, Fe or Co), Li2M 2 SO4(M 2 =Mn, Fe or Co), LiM2SO4 m F (M2 = Fe, Mn or Co), Li 2-x (Fe 1-y Mn y )P2O7(0≤x≤1;0≤y≤1), Li3V 2-x M1 x (PO4)3(M1=Cr, Co, Fe, Mg, Y, Ti, Nb or Ce; 0≤x≤1); Li 4-x M x Ti5O 12 (M=Mg, Al, Ba, Sr or Ta; 0≤x≤1); LiCoO2; LiFePO4(LFP); LiMC1 x MC2 1-x O2 (MC1 and MC2 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al; 0≤x≤1); LiMC1 x MC2 1-x PO4(MC1 or MC2=Fe, Mn, Ni, Co, Cr or Ti; 0≤x≤1); LiMC1 x MC2 y MC3 1-x-y O2 (MC1, MC2 and MC3 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al respectively; 0≤x≤1; 0≤y≤1, 0≤x+y≤1); LiMn2O4 (LMO); LiMn 2-y X y O4(X=Cr, Al or Fe, 0≤y≤1); LiNi 0.5 Mn 1.5 O4 spinel; LiNi 0.5-y X y Mn 1.5 O4 (X=Fe, Cr, Zn, Al, Mg, Ga, V or Cu; 0≤y<0.5); LiNi 0.8 Co 0.15 Al 0.05 O2(NCA);LiNi x Mn y Co Z O2 (NMC, x+y+z=1), Li-rich Li 1+w Ni x Mn y Co Z O2(x+y+z+w=1,0≤w≤0.25); LiV3O8; LiVPO4F; MnO2; thionyl chloride; V2O5; V6O1; xLi2MnO3·(1-x)LiM 1 y M 2 M 3 1-y-z O2, where M 1 、M 2 and M 3 Mn, Ni, Co, Cr, Fe or a mixture thereof, respectively; and wherein x=0.3-0.5; y≤0.5; z≤0.5; or LiCl.

[0219] Preferably, the lithium ion cathode (6) has a lithiation level of 91 to 99%, more preferably 92 to 98%, even more preferably 93 to 97%, still more preferably 94 to 96% and most preferably 95%.

[0220] Battery

[0221] In yet another aspect, the present disclosure relates to a battery comprising at least one lithium-ion battery cell according to any of the foregoing embodiments of any of the foregoing aspects. An advantage of such a battery is that the mass of such a battery can be lower than that of the prior art while still having the same nominal voltage and capacity. In the context of the present disclosure, a battery may comprise one or more lithium-ion battery cells.

[0222] Battery shape

[0223] Examples of such batteries are cylindrical batteries, prismatic batteries, pouch batteries, and coin batteries. Several configurations of lithium-ion battery cells can also be combined. For example, a coin cell can have an internal cylindrical configuration (as disclosed in international patent application WO2015188959A1), or a pouch cell can have an internal prismatic configuration.

[0224] Typically, lithium-ion secondary batteries are manufactured as follows. First, a positive electrode and a negative electrode are provided. Subsequently, in order to manufacture a battery cell having a predetermined shape, a plurality of positive electrode plates and a plurality of negative electrode plates are stacked in a state where a separator is sandwiched between the positive electrode plate and the negative electrode plate, respectively. Subsequently, the battery cell is placed in a battery housing, and an electrolyte is provided to the battery housing. The battery housing is then typically sealed, thereby producing a battery, such as a battery pack.

[0225] The electrode lead is connected to the common electrode assembly. Each electrode lead is configured to have a structure in which one end of the electrode lead is connected to the electrode assembly, the other end of the electrode lead is exposed to the outside of the battery case, and the battery case in which the electrode assembly is placed is sealed by an adhesive layer such as a sealant layer at a portion of the battery case where the electrode lead extends outward from the battery case.

[0226] In addition, the electrode assembly is provided with an electrode tab. Each collector plate of the electrode assembly includes a coated portion coated with an electrode active material and an end portion (hereinafter referred to as a "non-coated portion") that may not be coated with an electrode active material. Each electrode tab can be formed by connecting an uncoated portion, or preferably by connecting a separate conductive tab connected to the electrode, and even more preferably by ultrasonic welding. These electrode tabs may protrude in one direction so that the electrode tabs are formed at the electrode assembly in a side-by-side arrangement. Alternatively, the electrode tabs may protrude in opposite directions. Each electrode tab is then conveniently used as a path for electrons to move between the inside and outside of the battery. In addition, each electrode lead is preferably connected to the corresponding electrode tab by spot welding.

[0227] The electrode leads may extend in the same direction or in opposite directions, depending on where the positive electrode tab and the negative electrode tab are formed. The positive electrode lead and the negative electrode lead may be made of different materials. Finally, the electrode lead is electrically connected to an external terminal via its terminal portion.

[0228] The bag-like sheath member includes an electrode assembly in a sealed state so that a portion of each electrode lead (e.g., a terminal portion of each electrode lead) is exposed from the bag-like sheath member. As previously described, an adhesive layer (such as a sealant layer) is sandwiched between each electrode lead and the bag-like sheath member. The bag-like sheath member is provided with a sealing area at its edge. The horizontal slit of each electrode lead is spaced apart from the sealing area toward the joint. That is, when each electrode lead is formed to have an inverted T-shape, the legs of the T-shape protrude outward from the bag-like sheath member, and a portion of the head of the T-shape is located in the sealing area.

[0229] Prismatic battery

[0230] In a preferred embodiment, the battery is approximately rectangular in shape with a height of 48.5 mm, a length of 26.5 mm and a width of 17.5 mm. Preferably, the battery has a nominal voltage of 9 volts. Preferably, the battery is rechargeable.

[0231] In another embodiment, the present disclosure relates to a rectangular battery comprising a battery cell according to any of the preceding embodiments of any of the preceding aspects. Preferably, the rectangular battery is selected from: a 4.5 volt lantern battery, a 6 volt (spring or screw fitting) lantern battery; a 7.5 volt lantern battery; a 12 volt lantern battery; or a 9 volt battery.

[0232] Cylindrical battery

[0233] A cylindrical lithium-ion secondary battery typically comprises a spirally wound electrode assembly comprising a cathode and an anode between which a separator is spirally wound, and a pair of insulating plates in a substantially hollow cylindrical battery can. In a preferred embodiment, the battery is a cylindrical battery having a diameter of 17 mm and a height of 34.5 mm. Preferably, the battery has a nominal voltage of 3.6 volts. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 700 mAh. Preferably, the battery is rechargeable.

[0234] In a preferred embodiment, the battery has a cylindrical shape with a diameter of 15.6 mm and a length of 27 mm. Preferably, the battery has a nominal voltage of 3.6 volts. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 600 mAh or 800 mAh. Preferably, the battery is rechargeable.

[0235] In a preferred embodiment, the battery is a cylindrical battery with a diameter of 17 mm and a height of 34.5 mm. Preferably, the battery has a nominal voltage of 3.6 volts. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 700 mAh.

[0236] Double cylindrical battery

[0237] In a preferred embodiment, the battery has a dual cylindrical shape with a height of 52.20 mm, a length of 28.05 mm, and a width of 14.15 mm. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 1300 mAh.

[0238] Button battery

[0239] Button cells are also commonly referred to as coin cells, which are thin compared to their diameter. In a preferred embodiment, the battery is a button cell having a diameter of 9.5 mm and a height of 2.7 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts, or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 30 mAh for continuous discharge to 2.0 volts per cell.

[0240] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 10 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 30 mAh for continuous discharge to 2.0 volts per cell.

[0241] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 11.5 mm and a height of 3.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. And a capacity of 70 mAh for continuous discharge to 2.0 volts per cell.

[0242] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 11 mm and a height of 10.8 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 160 mAh for continuous discharge to 2.0 volts per cell.

[0243] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 12.5 mm and a height of 1.6 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 25 mAh for continuous discharge to 2.0 volts per cell.

[0244] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 12.5 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 35 mAh to 40 mAh for continuous discharge to 2.0 volts per cell.

[0245] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 12.5 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 50 mAh for continuous discharge to 2.0 volts per cell.

[0246] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 16 mm and a height of 1.6 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 50 mAh to 55 mAh for continuous discharge to 2.0 volts per cell.

[0247] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 16 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 75 mAh to 78 mAh for continuous discharge to 2.0 volts per cell.

[0248] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 16 mm and a height of 3.2 mm.

[0249] Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts.

[0250] More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 140 mAh for continuous discharge to 2.0 volts per cell.

[0251] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 1.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 55 mAh for continuous discharge to 2.0 volts per cell.

[0252] In a preferred embodiment, the battery is a button-shaped cell having a diameter of 20 mm and a height of 1.6 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 90 mAh for continuous discharge to 2.0 volts per cell. In a preferred embodiment, the battery is a button-shaped cell having a diameter of 20 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 115 mAh to 125 mAh for continuous discharge to 2.0 volts per cell.

[0253] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 160 mAh to 165 mAh for continuous discharge to 2.0 volts per cell.

[0254] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 3.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 225 mAh for continuous discharge to 2.0 volts per cell. Preferably, the battery has a maximum discharge current of 3 mA. Preferably, the battery has a maximum pulse discharge current of 15 mA. Preferably, the battery has a mass of less than 3.0 g, more preferably less than 2.9 g, even more preferably less than 2.8 g.

[0255] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 4.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 280 mAh for continuous discharge to 2.0 volts per cell.

[0256] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 350 mAh for continuous discharge to 2.0 volts per cell.

[0257] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 110 mAh-175 mAh for continuous discharge to 2.0 volts per cell.

[0258] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 165 mAh to 210 mAh for continuous discharge to 2.0 volts per cell. In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 3.0 mm.

[0259] Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 265 mAh for continuous discharge to 2.0 volts per cell.

[0260] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 3.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 165 mAh for continuous discharge to 2.0 volts per cell.

[0261] In a preferred embodiment, the battery is a button-shaped battery with a diameter of 23 mm and a height of 5.4 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 560 mAh for continuous discharge to 2.0 volts per battery cell. In a preferred embodiment, the battery is a button-shaped battery with a diameter of 24 mm and a height of 1.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 100 mAh for continuous discharge to 2.0 volts per battery cell. In a preferred embodiment, the battery is a button-shaped battery with a diameter of 24 mm and a height of 3.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 270 mAh to 290 mAh for sustained discharge to 2.0 volts per cell.

[0262] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 24 mm and a height of 5.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 610 mAh to 620 mAh for continuous discharge to 2.0 volts per cell.

[0263] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 24 mm and a height of 7.7 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 1000 mAh for continuous discharge to 2.0 volts per cell. In a preferred embodiment, the battery is a button-shaped battery having a diameter of 26.2 mm and a height of 1.67 mm.

[0264] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 30 mm and a height of 3.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 500 mAh to 560 mAh for continuous discharge to 2.0 volts per cell.

[0265] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 30 mm and a height of 3.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts, 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 500 mAh to 560 mAh for continuous discharge to 2.0 volts per cell.

[0266] Flat or bag-shaped

[0267] The design of a single cell around a high energy positive electrode active material can provide a battery with a high capacity within a practical form. Pouch cells are typically approximately rectangular, excluding connecting tabs and other potential features around the edges, characterized by a thickness (t) and a planar area having a width (w) and a height (h), wherein the thickness is typically significantly smaller than the linear dimensions (width and height) defining the planar area (w·h). In particular, the battery can have a thickness between about 7 mm and about 18 mm. The area of ​​the pouch cell can be in the range of about 25,000 mm2 to about 50,000 mm2, wherein the linear dimensions of the width and height defining the area are typically in the range of about 50 mm to about 750 mm.

[0268] When discharged from 4.5V to 2.0V, the resulting single cell can typically have a discharge energy density of at least about 160Wh / kg. In some advantageous embodiments, when discharged from 4.5V to 2.0V, the resulting battery can have a discharge energy density of at least about 200Wh / kg, and in other embodiments, about 250Wh / kg to about 400Wh / kg. In other embodiments, the battery can have a volumetric discharge energy density of at least about 300Wh / l. In other advantageous embodiments, when discharged from 4.5V to 2.0V, the resulting battery can have a volumetric discharge energy density of at least about 500Wh / l to 1150Wh / l.

[0269] In the above embodiments, a battery of a prismatic, cylindrical, laminated film, coin or button type or spirally wound configuration is described. However, the battery according to the present invention can be applied to any other shape, wherein the battery element has any other configuration such as a laminated configuration.

[0270] Use of a battery cell or battery according to any preceding aspect

[0271] Another aspect of the present disclosure is the use of a battery cell or battery according to any preceding aspect or embodiment of the present disclosure as an energy storage and / or release device.

[0272] The term "energy storage and / or release device" herein is understood to refer to a secondary battery, including an electrode assembly of a cathode / separator / anode structure mounted in a suitable battery case. Such batteries include lithium-ion secondary batteries, which excel in providing high energy density and high capacity; and their use in secondary battery modules including a plurality of secondary batteries, which are typically connected in series to form a battery pack, which can be incorporated into a housing to form a module.

[0273] Detailed description of the drawings

[0274] The present disclosure will now be discussed with reference to the accompanying drawings, which show preferred exemplary embodiments of the present disclosure.

[0275] Figure 1 A method for manufacturing a lithium-ion battery cell according to the present disclosure is schematically depicted. The figure shows a preferred embodiment of the process of the present invention for constructing a lithium-ion battery cell, such as a pouch cell (10), by stacking the following components for a pre-lithiation step: first providing (i) an anode material, and (ii) a ceramic-coated separator (2), such as a polymer polyolefin coated with an aluminum oxide layer on both sides; (iii) a sacrificial cathode material (4), such as a lithium source, such as a lithium nickel manganese cobalt oxide material; (iv) a plastic separator (5); and (v) a non-sacrificial cathode material (3). The silicon layer of the anode material (6) is oriented to face the separator (2). Then, both the sacrificial cathode (4) and the silicon anode (6) are connected to an external circuit via electrode tabs (8, 9) connected to the electrodes (4, 6) in an electrically conductive manner. The tabbed and stacked cells are encapsulated in a commercially available encapsulation material and sealed on three sides. An electrolyte of commercial origin is added to the encapsulation (10) under a dry atmosphere, and the encapsulation is then sealed under reduced pressure.

[0276] The cell (10) so formed is then charged to a suitable rate, for example 250 mAh / g at 0.2C, to provide a partially charged encapsulated cell (11) comprising a pre-lithiated silicon anode (1).

[0277] The sacrificial cathode (4) is then disconnected from the external circuit, and the sacrificial cathode (4) and the plastic separator (5) are removed from the partially charged battery cell (11). A non-sacrificial cathode (3) is then provided, which is connected to the external circuit via an electrode tab (7) connected to the electrode (3) in a conventional manner. A separator (2) is provided to separate the pre-lithiated anode material (1) and the non-sacrificial cathode (3). The residual electrolyte then provides an electrochemical bridge between the pre-lithiated anode material (1) and the non-sacrificial cathode (3) through the separator (2). The resulting encapsulated battery cell (12) is then typically sealed under reduced pressure to obtain the desired lithium battery cell.

[0278] Figure 2A is a top-down scanning electron microscope image obtained from an anode including a silicon layer, wherein the silicon layer includes a plurality of columnar structures. The scale bar corresponds to 50 μm, wherein each scale mark corresponds to 5 μm.

[0279] Figure 2B is a cross-sectional scanning electron microscope image obtained from an anode including a silicon layer, wherein the silicon layer includes a plurality of columnar structures. The scale bar corresponds to 10 μm, wherein each scale mark corresponds to 1 μm.

[0280] Figure 3 3A, solid line). Example 3 (battery cell according to the present invention) exhibits a lower charge voltage and a higher discharge voltage than Comparative Example 3A. Therefore, Example 3 exhibits higher energy efficiency than Comparative Example 3A.

[0281] Figure 4 is a graph of capacity (Ah) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3, dashed line) and comparative examples (Example 3A, solid line). The lithium-ion battery cells according to the present disclosure exhibit improved capacity compared to the comparative examples.

[0282] Figure 5 is a graph of capacity retention (%) versus experimentally obtained cycle number for materials according to the present disclosure (Example 3) and comparative examples (Example 3A). The lithium ion battery cell according to the present disclosure exhibits improved capacity retention compared to the comparative examples.

[0283] Figure 6 is a graph of specific capacity (Ah / g) versus experimentally obtained cycle number for materials according to the present disclosure (Example 3, dashed line) and comparative examples (Example 3A, two nearly overlapping solid lines). The lithium-ion battery cells according to the present disclosure exhibit improved specific capacity compared to the comparative examples.

[0284] Figure 7 is the area capacity (mAh / cm 2 ) versus the number of cycles experimentally obtained for materials according to the present disclosure (Example 3, dashed line) and the comparative example (Example 3A, two nearly overlapping solid lines). The lithium-ion battery cell according to the present disclosure exhibits improved areal capacity compared to the comparative example.

[0285] Figure 83 is a graph of cumulative specific capacity (Ah / g) versus experimentally obtained cycle number for materials according to the present disclosure (Example 3, dashed line) and comparative example (Example 3A, two nearly overlapping solid lines). The cumulative specific capacity for lithium ions according to the present disclosure up to 80% life start capacity is increased by about 1.4 times compared to the comparative example.

[0286] Fig.9A is the specific energy (mWh / cm 2 ) is a graph of the number of cycles experimentally obtained for materials according to the present disclosure (Example 3, dashed line) and the comparative example (Example 3A, two nearly overlapping solid lines). The lithium-ion battery cell according to the present disclosure exhibits an increase in specific energy of about 13% compared to the comparative example.

[0287] Fig. 9B is a graph of energy efficiency (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3, upper set of data points) and comparative examples (Example 3A, lower set of data points). For almost every cycle, the material according to the present disclosure has a higher energy efficiency than the comparative material. The lithium-ion battery cell according to the present disclosure exhibits a 1% improvement in energy efficiency compared to the comparative example.

[0288] Fig.10 is a graph of (i) the number of charging cycles that can be performed until only 80% of the initial capacity of the full cell is obtained [“Number of cycles at 80% capacity retention” in Table 1]; versus (ii) the lithium reserve divided by the lithium utilization. The lithium reserve is an indirect measure of the degree of pre-lithiation, with higher numbers corresponding to higher degrees of pre-lithiation. In this example, the lithium reserve value of 686 mAh / g corresponds to 19% of the theoretical maximum. The lithium reserve is the lithium content in the silicon in the discharged state of the full cell, normalized to the mass of silicon in the silicon anode. The lithium utilization is the amount of lithium used during cycling, normalized to the mass of silicon in the silicon anode. A favorable linear relationship is observed between: (i) the number of charging cycles that can be performed until only 80% of the initial capacity of the full cell is obtained; versus (ii) the lithium reserve divided by the lithium utilization.

[0289] List of reference numerals

[0290] 1 Pre-lithiation silicon anode

[0291] 2 Partition

[0292] 3 Non-sacrificial cathode

[0293] 4 Sacrificial lithium-ion cathode

[0294] 5 Divider

[0295] 6 Silicon Anode

[0296] 7 Non-sacrificial cathode electrode tab

[0297] 8 Sacrificial cathode electrode tab

[0298] 9 (Pre-lithiation) Silicon anode electrode tab

[0299] 10 First intermediate battery unit

[0300] 11 Second intermediate battery unit

[0301] 12 Lithium-ion battery cells

[0302] A charges the intermediate lithium-ion battery cell (10)

[0303] B removes the sacrificial lithium ion cathode (4) and separator (5).

[0304] Example

[0305] The following non-limiting examples illustrate products and processes according to the present disclosure.

[0306] Example 1 - Preparation of a silicon anode suitable for lithiation [silicon with columnar morphology at the nanoscale]

[0307] A roll of roughened copper foil current collector material (Sa 0.51 μm, Sq 0.65 μm, Sz 5.9 μm, Sds 0.77 μm) was placed on the -2 , SSC 16.2μm-2, SDQ 2.1μm, Sdr 157%, as determined by standard method ISO 25178) is fed into a plasma enhanced chemical vapor deposition (PECVD) equipment, which includes an unwinding chamber, two deposition chambers and a rewinding chamber. These chambers are all connected and usually operate under vacuum (0.05 mbar-0.2 mbar). The foil is transported by a tension roller system and two heating drums that control the foil temperature. At a substrate temperature of 100°C to 300°C, the first silicon layer is deposited by PECVD onto the same side of the copper substrate. In this process, magnetron radiation with a frequency of 2.45GHz is used to excite a gas mixture containing a silicon precursor gas and a supporting gas. Silane (SiH4) is the source of silicon, while argon (Ar) and hydrogen (H2) are added to stabilize the plasma, affect the material structure and increase the deposition rate. The gas is injected via a "gas shower" that evenly distributes the gas.

[0308] Magnetron (microwave) radiation is introduced into the vacuum chamber with the aid of an antenna. To ensure a uniform plasma, both sides of the antenna are connected to a source of magnetron radiation. Magnetron heads are therefore located on each side of the antenna. These magnetron heads are connected to the antenna. Gas is injected via a gas shower close to the magnetron heads. The antenna is protected from the reaction environment by a quartz tube. The plasma is confined by a magnetic field generated by an array of permanent magnets.

[0309] The silicon production rate is determined by the process conditions, the power input to each source and the number of microwave sources in operation. The gas flow rate is proportional to the MW power input, which is 800W / m-6000W / m. Ten antennas or power inputs are used.

[0310] Figure 2A is a top-down scanning electron microscope (SEM) image of the obtained material. Figure 2B is a cross-sectional scanning electron microscope (SEM) image of the obtained material.

[0311] Cross-sectional SEM ( Figure 2B ) determined that the deposited silicon layer had a thickness of 8 to 9 μm. BET analysis determined that the material had a surface area of ​​79.9 m 2 / g, the porosity is 15.73%, and the average pore size is 4.01nm. XRF analysis shows that the mass loading is 1.27mg / cm 2 -1.29mg / cm 2 The deposited material had a CIELAB lightness value L* of 42.07 to 42.98.

[0312] Example 2 - Electrochemical Pre-lithiation of Silicon Anode

[0313] A pouch cell was constructed by stacking (i) anode material as prepared above [Example 1], (ii) a ceramic coated separator (12 μm polymer polypropylene coated on both sides with 2 μm alumina layers from Gelon LIB Group, China), and (iii) a sacrificial cathode material (3.5 Ah / cm 2Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material). The silicon layer is oriented to face the separator. Both the cathode and the anode are connected to the external circuit via electrode tabs, which are welded to the electrodes by conventional methods. The tabbed and stacked units are bagged in commercially available laminated aluminum bag material, which is sealed on three sides. A commercially sourced electrolyte [a solution of LiPF6 (1 M) in a mixture of 4-fluoro-1,3-dioxolane-2-one (fluoroethylene carbonate, FEC) and diethyl carbonate (DEC) in a volume ratio of 3:7, the mixture additionally containing 2 wt.% of vinylene carbonate (VC) and 2 wt.% of adiponitrile (AN)] is added to the laminated aluminum bag under a dry atmosphere and then vacuum sealed.

[0314] The pouch cells were charged at a rate of about 0.2C to 250 mAh / g (7% of the theoretical maximum).

[0315] The pouch cell is then disconnected and the pre-lithiated anode is isolated.

[0316] Example 3 - Method of making a battery cell with pre-lithiated silicon anode material

[0317] The process is as Figure 1 Schematically depicted in .

[0318] A pouch cell (10) was constructed by stacking: (i) anode material (6) prepared as described above in [Example 1]; (ii) a ceramic coated separator (2) (12 μm polymer polypropylene coated on both sides with a 2 μm alumina layer from Gelon LIB Group, China); (iii) a sacrificial cathode material (4) (3.5 Ah / cm 2 Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material); (iv) a plastic separator (5); and (v) a non-sacrificial cathode material (3) (3.5 Ah / cm 2Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material). The silicon layer of the anode material (6) is oriented toward the separator (2). Both the sacrificial cathode (4) and the silicon anode (6) are connected to an external circuit via electrode tabs (8, 9), which are welded to the electrodes (4, 6) by conventional methods. The tabbed and stacked units are bagged in a commercially available laminated aluminum bag material, which is sealed on three sides. A commercially sourced electrolyte [a solution of LiPF6 (1 M) in a mixture of 4-fluoro-1,3-dioxolane-2-one (fluoroethylene carbonate, FEC) and diethyl carbonate (DEC) in a volume ratio of 3:7, the mixture additionally containing 2 wt.% of vinylene carbonate and 2 wt.% of adiponitrile (AN)] is added to the laminated aluminum bag (10) under a dry atmosphere and then vacuum sealed.

[0319] The pouch cell (10) was charged at 0.2C to 250 mAh / g (7% of the theoretical maximum) to provide a partially charged pouch cell (11) comprising a pre-lithiated silicon anode (1).

[0320] The sacrificial cathode (4) is disconnected from the external circuit. The sacrificial cathode (4) and the plastic separator (5) are removed from the partially charged pouch cell (11). The non-sacrificial cathode (3) is connected to the external circuit via an electrode tab (7) which is welded to the electrode (3) by conventional methods. The separator (2) separates the pre-lithiated anode material (1) and the non-sacrificial cathode (3). The residual electrolyte electrochemically bridges the pre-lithiated anode material (1) and the non-sacrificial cathode (3) through the separator (2). The resulting pouch cell (12) is then vacuum sealed.

[0321] Comparative Example 3A - Method of Making a Comparative Battery Cell

[0322] A pouch cell was constructed by stacking: (i) anode material prepared as above [Example 1]; (ii) ceramic coated separator (12 μm polymer polypropylene coated on both sides with 2 μm alumina layer from Gelon LIB Group, China); (iii) cathode material (3.5 Ah / cm 2Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material). The silicon layer is oriented to face the separator. Both the cathode and the anode are connected to the external circuit via electrode tabs, which are welded to the electrodes by conventional methods. The tabbed and stacked units are bagged in commercially available laminated aluminum bag material, which is sealed on three sides. A commercially sourced electrolyte [a solution of LiPF6 (1 M) in a mixture of 4-fluoro-1,3-dioxolane-2-one (fluoroethylene carbonate, FEC) and diethyl carbonate (DEC) in a volume ratio of 3:7, the mixture additionally containing 2 wt.% of vinylene carbonate and 2 wt.% of adiponitrile (AN)] is added to the laminated aluminum bag under a dry atmosphere and then vacuum sealed.

[0323] The pouch cell was not charged prior to any subsequent testing.

[0324] Example 3B - Fabrication of a pre-lithiated silicon anode material [2.5 Ah / cm 2 Cathode] battery cell method

[0325] A pouch cell was constructed by stacking: (i) anode material prepared as above [Example 1]; (ii) a ceramic coated separator (12 μm polymer polypropylene coated on both sides with 2 μm alumina layers from Gelon LIB Group, China); (iii) a sacrificial cathode material (2.5 Ah / cm 2 Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material); (iv) a plastic separator; and (v) a non-sacrificial cathode material (2.5 Ah / cm 2 Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material). The silicon layer is oriented to face the separator. Both the sacrificial cathode and anode are connected to the external circuit via electrode tabs, which are welded to the electrodes by conventional methods. The tabbed and stacked units are bagged in commercially available laminated aluminum bag material, which is sealed on three sides. A commercially sourced electrolyte [a solution of LiPF6 (1 M) in a mixture of 4-fluoro-1,3-dioxolane-2-one (fluoroethylene carbonate, FEC) and diethyl carbonate (DEC) in a volume ratio of 3:7, the mixture additionally containing 2 wt.% of vinyl carbonate and 2 wt.% of adiponitrile (AN)] is added to the laminated aluminum bag under a dry atmosphere and then vacuum sealed.

[0326] The pouch cells were pre-lithiated to between 0 mAh / g and 1200 mAh / g (1 / 3 of the theoretical maximum) and then charge cycled between 0 mAh / g and 1200 mAh / g at a rate of 0.1 C for initial cycles and tested at a rate of 0.2 C for subsequent cycles.

[0327] The sacrificial cathode is disconnected from the external circuit. The sacrificial cathode and plastic separator are removed from the pouch cell. The non-sacrificial cathode is connected to the external circuit via an electrode tab, which is welded to the electrode by conventional methods. The separator separates the anode material and the non-sacrificial cathode. The residual electrolyte electrochemically bridges the pre-lithiated anode material and the non-sacrificial cathode through the separator. The pouch cell is then vacuum sealed.

[0328] Example 3C - Fabrication of a pre-lithiated silicon anode material [3.5 Ah / cm 2 Method for battery cell having cathode

[0329] A pouch cell was constructed by stacking: (i) anode material prepared as above [Example 1]; (ii) a ceramic coated separator (12 μm polymer polypropylene coated on both sides with 2 μm alumina layers from Gelon LIB Group, China); (iii) a sacrificial cathode material (2.5 Ah / cm 2 Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material); (iv) a plastic separator; and (v) a non-sacrificial cathode material (3.5 mAh / cm 2 Lithium nickel manganese cobalt oxide NMC 622, commercially available from TOP Material). The silicon layer is oriented to face the separator. Both the sacrificial cathode and anode are connected to the external circuit via electrode tabs, which are welded to the electrodes by conventional methods. The tabbed and stacked units are bagged in commercially available laminated aluminum bag material, which is sealed on three sides. A commercially sourced electrolyte [a solution of LiPF6 (1 M) in a mixture of 4-fluoro-1,3-dioxolane-2-one (fluoroethylene carbonate, FEC) and diethyl carbonate (DEC) in a volume ratio of 3:7, the mixture additionally containing 2 wt.% of vinylene carbonate and 2 wt.% of adiponitrile (AN)] is added to the laminated aluminum bag under a dry atmosphere and then vacuum sealed.

[0330] The pouch cells were pre-lithiated to between 0 mAh / g and 1200 mAh / g (1 / 3 of the theoretical maximum) and then charge cycled between 0 mAh / g and 1200 mAh / g at a rate of 0.1 C for initial cycles and tested at a rate of 0.2 C for subsequent cycles.

[0331] The sacrificial cathode is disconnected from the external circuit. The sacrificial cathode and plastic separator are removed from the pouch cell. The non-sacrificial cathode is connected to the external circuit via an electrode tab, which is welded to the electrode by conventional methods. The separator separates the anode material and the non-sacrificial cathode. The residual electrolyte electrochemically bridges the pre-lithiated anode material and the non-sacrificial cathode through the separator. The pouch cell is then vacuum sealed.

[0332] Example 3D - Fabrication of a pre-lithiated silicon anode material [4.5 mAh / cm 2 Cathode] battery cell method

[0333] The pouch cell is the same as Example 3C except that the sacrificial cathode and non-sacrificial cathode are 4.5 mAh / cm -2 Lithium nickel manganese cobalt oxide NMC 622 cathode, commercially available from TOP Material.

[0334] The pouch cells were pre-lithiated to between 0 mAh / g and 1200 mAh / g (1 / 3 of the theoretical maximum) and then charge cycled between 0 mAh / g and 1200 mAh / g at a rate of 0.1 C for initial cycles and tested at a rate of 0.2 C for subsequent cycles.

[0335] The sacrificial cathode is disconnected from the external circuit. The sacrificial cathode and plastic separator are removed from the pouch cell. The non-sacrificial cathode is connected to the external circuit via an electrode tab, which is welded to the electrode by conventional methods. The separator separates the anode material and the non-sacrificial cathode. The residual electrolyte electrochemically bridges the pre-lithiated anode material and the non-sacrificial cathode through the separator. The pouch cell is then vacuum sealed.

[0336] Example 4 - First Cycle Analysis

[0337] The pouch cells prepared according to Example 3 and Comparative Example 3A were charged and then discharged at 0.5C to 1700 mAh / g. Figure 3 As shown (charging on the left, discharging on the right).

[0338] Example 3 (battery cell according to the present invention) exhibits a lower charge voltage and a higher discharge voltage than Comparative Example 3 A. Therefore, Example 3 exhibits higher energy efficiency than Comparative Example 3A.

[0339] Example 5 - Cycle Life / Capacity Retention Analysis

[0340] The battery cells according to the present disclosure prepared according to Example 3 and the comparative battery cells prepared according to Example 3A were evaluated for their capacity retention properties.

[0341] The cycling conditions used were C / 2 rate, 3 V to 4.2 V at 25°C (constant voltage [CV] steps at 4.2 V up to C / 20 rate).

[0342] exist Figure 4 , Figure 5 , Figure 6 , Figure 7 and Figure 8 The results are presented in .

[0343] The results show that the lithium-ion battery cell according to the present disclosure shows that the lithium-ion battery cell according to the present disclosure:

[0344] - Maintains high areal capacity over significantly more charge cycles than comparative examples;

[0345] - Maintains high capacity retention over significantly more charge cycles than the comparative examples;

[0346] - Maintains high specific capacity over significantly more charge cycles than comparative examples;

[0347] - Maintain high areal capacity over significantly more charge cycles than comparative examples; and

[0348] - Maintains a substantially linear cumulative specific capacity relationship for significantly more charging cycles.

[0349] Thus, the lithium-ion battery cells according to the present disclosure exhibit improved capacity retention, and therefore improved cycle life, compared to lithium-ion battery cells made using conventional anodes. For lithium-ion battery cells according to the present disclosure, the number of cycles required for the cumulative specific capacity (down to 80% of the life capacity starting value) is approximately 40% higher than for lithium-ion battery cells made using conventional methods, where the cumulative specific capacity is a measure of how much capacity is normalized to the mass of silicon.

[0350] Example 6 - Cycle Life / Specific Energy

[0351] The battery cells according to the present disclosure prepared according to Example 3 and the comparative battery cells prepared according to Example 3A were evaluated for their specific energy properties.

[0352] The cycling conditions used were C / 2 rate, 3 V to 4.2 V at 25°C (constant voltage [CV] steps at 4.2 V up to C / 20 rate).

[0353] exist Figure 8 The results are presented in Figure 9.

[0354] The results show that the lithium-ion battery cell according to the present disclosure shows that the lithium-ion battery cell according to the present disclosure:

[0355] - Has 13% more specific energy (mWh / cm 2 );

[0356] - Demonstrated 1% higher energy efficiency (%) than the comparative example average during cycle life.

[0357] Example 7 - Cycle Life / Degree of Pre-lithiation

[0358] The capacity retention properties of the battery cells according to the present disclosure prepared according to Example 3B, Example 3C, and Example 3D were evaluated.

[0359] This analyses the number of cycles at which the capacity drops to 80% of the initial capacity as a function of lithium storage / lithium utilization.

[0360] The lithium reserve is the lithium content in the silicon at the discharged state of the full cell, normalized to the mass of silicon in the silicon anode. Increasing the degree of pre-lithiation increases the lithium reserve.

[0361] Lithium utilization is the amount of lithium used during cycling, normalized to the mass of silicon in the silicon anode.

[0362] The results are reproduced in Table 1 below and in Fig.10 The lithium reserve is an indirect measure of the degree of pre-lithiation, where a higher number corresponds to a higher degree of pre-lithiation. In this example, a lithium reserve value of 686 mAh / g corresponds to 19% of the theoretical maximum.

[0363] Table 1:

[0364]

[0365]

[0366] from Fig.10 It can be seen that a linear relationship between (lithium storage amount / lithium utilization amount) and cycle life is observed.

Claims

1. A method for manufacturing a lithium-ion battery cell (12), comprising the following steps: (i) providing a silicon anode (6); (ii) pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 1% to 100%; (iii) providing a supply: a separator (2); an electrolyte; and a lithium ion cathode (3); (iv) forming a lithium-ion battery cell from the pre-lithiated silicon anode (1), the separator (2) and the lithium-ion cathode (3), Wherein, the silicon anode (6) comprises: A lithium storage material, wherein the lithium storage material comprises between 70 wt.% and 100 wt.%, preferably between 85 wt.% and 100 wt.% silicon relative to the lithium storage material; wherein the lithium storage material comprises a silicon material having a columnar morphology; and Collector.

2. The method according to claim 1, wherein: The lithium storage material includes 90.0wt.% to 100.0wt.% silicon, more preferably 92.0wt.% to 99.8wt.% silicon, even more preferably 94.0wt.% to 99.6wt.% silicon, still more preferably 96.0wt.% to 99.4wt.% silicon, still more preferably 98.0wt.% to 99.2wt.% silicon and most preferably 99.0wt.% to 99.1wt.% silicon.

3. A method according to any preceding claim, wherein: The step of pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) is performed to achieve a pre-lithiation level of 2% to 80%, preferably 3% to 60%, even more preferably 5% to 40%, still more preferably 10% to 30% and most preferably 15% to 20%.

4. A method according to any preceding claim, wherein: The silicon anode (6) comprises a lithium storage material layer.

5. A method according to any preceding claim, wherein: The lithium storage material includes a silicon material having a nanoscale structure and a nanoscale columnar morphology on a surface.

6. A method according to any preceding claim, wherein: The step of pre-lithiating the silicon anode (6) to form a pre-lithiated silicon anode (1) is selected from one of the following methods: Electrochemically pre-lithiating the silicon anode (6) using a sacrificial lithium ion cathode (4); treating the silicon anode (6) with a sacrificial electrolyte salt; or Lithium is physically deposited on the silicon anode (6).

7. A method according to any preceding claim, wherein: The cathode is selected from the following: a carbon / sulfur composite or an air electrode, in particular a carbon-based electrode comprising graphitic carbon and optionally a metal catalyst such as Ir, Ru, Pt, Ag or Ag / Pd; carbon monofluoride; CuO (copper oxide); Cr2O5; Cr3O8; iron disulfide; Li2M 2 SiO4(M 2 =Mn, Fe or Co), Li2M 2 SO4(M 2 =Mn, Fe or Co), LiM2SO 4m F (M2 = Fe, Mn or Co), Li 2-x (Fe 1-y Mn y )P2O7 (0≤x≤1; 0≤y≤1), Li3V 2-x M1 x (PO4)3(M1=Cr, Co, Fe, Mg, Y, Ti, Nb or Ce; 0≤x≤1); Li 4-x M x Ti5O 12 (M=Mg, Al, Ba, Sr or Ta; 0≤x≤1); LiCoO2; LiFePO4(LFP); LiMC1 x MC 2 1-x O2 (MC1 and MC2 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al; 0≤x≤1); LiMC1 x MC2 1-x PO4(MC1 or MC2=Fe, Mn, Ni, Co, Cr or Ti; 0≤x≤1); LiMC1 x MC2 y MC3 1-x-y O2 (MC1, MC2 and MC3 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al respectively; 0≤x≤1; 0≤y≤1, 0≤x+y≤1); LiMn2O4 (LMO); LiMn 2-y X y O4(X=Cr, Al or Fe, 0≤y≤1); LiNi 0.5 Mn 1.5 O4 spinel; LiNi 0.5-y X y Mn 1.5 O4 (X=Fe, Cr, Zn, Al, Mg, Ga, V or Cu; 0≤y<0.5); LiNi 0.8 Co 0.15 Al 0.05 O2(NCA);LiNi x Mn y Co Z O2 (NMC, x+y+z=1), Li-rich Li 1+w Ni x Mn y Co Z O2(x+y+z+w=1,0≤w≤0.25); LiV3O8; LiVPO4F; MnO2; thionyl chloride; V2O5; V6O1; xLi2MnO3·(1-x)LiM 1 y M 2 M 3 1-y-z O2, where M 1 、M 2 and M 3 Respectively Mn, Ni, Co, Cr, Fe or a mixture thereof; and wherein x=0.3-0.5; y≤0.5; z≤0.

5.

8. A method according to any preceding claim, wherein: The electrolyte includes a lithium salt selected from the following items: LiAsF6, Li2SO4, LiBF4, LiBr, LiCF3SO3, LiCl, LiClO4, LiI, LiNO2, LiNO3, LiSCN, 2-trifluoromethyl-4,5-dicyanoimidazole lithium (CAS: 761441-54-7), (fluorosulfonyl) (trifluoromethylsulfonyl) imide lithium (LiFTFSI), bis (fluorosulfonyl) imide lithium (LiFSI); bis (oxalate) borate lithium (LiBOB), bis (pentafluoroethanesulfonyl) imide lithium (LiBETI), bis (trifluoromethanesulfonyl) imide lithium (LiTFSI), difluoro (oxalate) borate lithium (LiDFOB CAS: 409071-16-5), trifluoromethanesulfonate lithium (LiTf), LiPF6 or any combination thereof.

9. A method according to any preceding claim, wherein: The electrolyte includes a solvent selected from the group consisting of: (i) an ester; (ii) a sulfur-containing solvent; (iii) a phosphorus-containing solvent; (iv) an ether; (v) a nitrile; or (vi) any combination thereof.

10. A method according to any preceding claim, wherein: The silicon anode (6) is pre-lithiated to form a pre-lithiated silicon anode (1) having a pre-lithiation level of 2% to 80%, preferably 3% to 60%, even more preferably 5% to 40%, still more preferably 10% to 30% and most preferably 15% to 20%.

11. A lithium-ion battery cell (12) obtainable by any of the preceding claims.

12. A lithium-ion battery cell (12), comprising: A pre-lithiated silicon anode (3) having a pre-lithiation level of 1% to 100%, wherein the lithium storage material comprises a silicon material having a columnar morphology; Partition (4); Electrolytes (5); and Lithium ion cathode (6).

13. The lithium-ion battery cell (12) according to claim 12, wherein: The lithium ion cathode (6) has a lithiation level of 70% to 100%, preferably 90% to 100%.

14. The lithium-ion battery cell according to any one of claims 11 to 13, wherein: The pre-lithiated silicon anode (3) has a pre-lithiation level of 2% to 80%, preferably 3% to 60%, even more preferably 5% to 40%, still more preferably 10% to 30% and most preferably 15% to 20%.

15. The lithium-ion battery cell according to any one of claims 11 to 14, wherein: The lithium ion cathode (6) is selected from the following: a carbon / sulfur composite or an air electrode, in particular a carbon-based electrode comprising graphitic carbon and optionally a metal catalyst such as Ir, Ru, Pt, Ag or Ag / Pd; carbon monofluoride; CuO (copper oxide); Cr2O5; Cr3O8; iron disulfide; Li2M 2 SiO4(M 2 =Mn, Fe or Co), Li2M 2 SO4(M 2 =Mn, Fe or Co), LiM2SO 4m F (M2 = Fe, Mn or Co), Li 2-x (Fe 1-y Mn y )P2O7(0≤x≤1;0≤y≤1), Li3V 2-x M1 x (PO4)3(M1=Cr, Co, Fe, Mg, Y, Ti, Nb or Ce; 0≤x≤1); Li 4-x M x Ti5O 12 (M=Mg, Al, Ba, Sr or Ta; 0≤x≤1); LiCoO2; LiFePO4(LFP); LiMC1 x MC 2 1- x O2 (MC1 and MC2 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al; 0≤x≤1); LiMC1 x MC2 1-x PO4(MC1 or MC2=Fe, Mn, Ni, Co, Cr or Ti; 0≤x≤1); LiMC1 x MC2 y MC3 1-x-y O2 (MC1, MC2 and MC3 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al respectively; 0≤x≤1; 0≤y≤1, 0≤x+y≤1); LiMn2O4 (LMO); LiMn 2-y X y O4(X=Cr, Al or Fe, 0≤y≤1); LiNi 0.5 Mn 1.5 O4 spinel; LiNi 0.5-y X y Mn 1.5 O4 (X=Fe, Cr, Zn, Al, Mg, Ga, V or Cu; 0≤y<0.5); LiNi 0.8 Co 0.15 Al 0.05 O2(NCA);LiNi x Mn y Co Z O2 (NMC, x+y+z=1), Li-rich Li 1+w Ni x Mn y Co Z O2(x+y+z+w=1,0≤w≤0.25); LiV3O8; LiVPO4F; MnO2; thionyl chloride; V2O5; V6O1; xLi2MnO3·(1-x)LiM 1 y M 2 M 3 1-y-z O2, where M 1 、M 2 and M 3 Respectively Mn, Ni, Co, Cr, Fe or a mixture thereof; and wherein x=0.3-0.5; y≤0.5; z≤0.

5.

16. Use of a lithium-ion battery cell (12) according to any one of claims 11 to 15 for storing and / or releasing energy.

17. A battery comprising a lithium-ion battery cell (12) according to any one of the preceding claims 11 to 15.

18. Use of a battery according to claim 17 as an energy storage and / or release device.

Citation Information

Patent Citations

  • Pre-lithiation method for anode for secondary battery

    EP3561918A1

  • Methods for prelithiation of silicon containing electrodes

    US20210104737A1

  • Pre-Lithiated Silicon-Based Anode, and Manufacturing Method Thereof

    US20210126250A1

  • Electrode including nanostructures for rechargeable cells

    WO2010129910A2

  • Structurally controlled deposition of silicon onto nanowires

    WO2015175509A1